2020
DOI: 10.3390/ijms21124414
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-Metabolism and Microenvironment in Cancer: Key Players for Immunotherapy

Abstract: Immune checkpoint inhibitors (ICIs) have changed therapeutic algorithms in several malignancies, although intrinsic and secondary resistance is still an issue. In this context, the dysregulation of immuno-metabolism plays a leading role both in the tumor microenvironment (TME) and at the host level. In this review, we summarize the most important immune-metabolic factors and how they could be exploited therapeutically. At the cellular level, an increased concentration of extracellular adenosine as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 160 publications
(220 reference statements)
0
93
0
Order By: Relevance
“…The results showed that high immunoscore was significantly correlated with the infiltration levels of B cells, CD4+ T cells, dendritic cells, macrophages, and neutrophils ( P < 0.05). Previous studies have proven the prognostic function in terms of these immune cells [ 19 21 ]. Recently, an extensive immunogenomic study using data compiled by TCGA was performed and included more than 10,000 tumors comprising 33 diverse cancer types [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that high immunoscore was significantly correlated with the infiltration levels of B cells, CD4+ T cells, dendritic cells, macrophages, and neutrophils ( P < 0.05). Previous studies have proven the prognostic function in terms of these immune cells [ 19 21 ]. Recently, an extensive immunogenomic study using data compiled by TCGA was performed and included more than 10,000 tumors comprising 33 diverse cancer types [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trp catabolism is involved in physiological immune suppression through the tryptophan–kynurenine–aryl hydrocarbon receptor (Trp–Kyn–AhR) pathway, and is involved in acquired and intrinsic resistance to immunotherapy [ 40 , 41 ]. Activated T-cells are extremely sensitive to the concentration of Trp in the peripheral environment, which triggers the effector T-cell apoptosis [ 42 ].…”
Section: Nutrients Affecting the Cellular Activity Of Immune Cellsmentioning
confidence: 99%
“…The production of adenosine lies in two significant pathways. The first pathway generates adenosine via the hydrolysis of extracellular ATP (eATP) by ectonucleotidases such as CD39 and CD73 [ 41 ]. The second pathway produces eAMP by a reaction that uses NAD+ as a substrate, catalyzed by the activity of both of CD38 (an NAD+ ectohydrolase) and CD203a (an ectonucleotide pyrophosphatase).…”
Section: Mechanisms and Pathways Modulating Metabolism And Affectimentioning
confidence: 99%
“…Furthermore, the expression of PD-1 by T regs increases their immunosuppressive ability. Interactions between these PD-1 expressing cells represent the main tumor immune escape mechanism mediated by these pathways in most solid cancers, including gynecological tumors [ 67 , 68 , 69 ]. A high expression of PD-L1, the main ligand of PD-1, is associated with increased clinical response rates and superior survival outcomes after treatment with ICIs in different tumors such as non small lung cancer and urothelial carcinomas [ 70 , 71 , 72 , 73 ].…”
Section: Immunopathology Of Vcmentioning
confidence: 99%